Pengaruh Pengungkapan Corporate Social Responsibility (CSR), Ukuran Perusahaan, dan Leverage Terhadap Kinerja Keuangan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017 – 2019) - Dewi, Afia Kusuma; Teti Chandrayanti; Sri Yuli Ayu Putri (Fakultas Ekonomi, Universitas Ekasakti, 2023)
This study aims to determine the effect of CSR Disclosure, Company Size and Leverage on Financial Performance in Manufacturing Companies listed on the IDX in 2017-2019. The data collection method in research uses data collected from financial reports that have been published on the IDX web. This study shows the results that: 1) Disclosure of Corporate Social Responsibility (CSR) has no partially significant effect on Financial Performance in Manufacturing Companies listed on the IDX in 2017-2019. 2) Company size has a partially significant influence on the Financial Performance of Manufacturing Companies listed on the IDX in 2017-2019. 3) Leverage has a partially significant effect on the Financial Performance of Manufacturing Companies listed on the IDX in 2017-2019. 4) Disclosure of CSR, Company Size and Leverage have a simultaneous significant effect on the Financial Performance of Manufacturing Companies listed on the IDX in 2017-2019.